2017
DOI: 10.1111/ijd.13857
|View full text |Cite
|
Sign up to set email alerts
|

Association between atopic dermatitis and squamous cell carcinoma: a case–control study

Abstract: Our findings support an increased risk of SCC development in the setting of AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 22 publications
0
29
0
1
Order By: Relevance
“…The most common serious TEAEs included squamous cell carcinoma of the skin. Of note, an increased incidence of non-melanoma skin cancers in patients with AD has been reported in the literature [24][25][26]. [14,19] (N = 7); NCT01859988 [20] (N = 296); NCT01385657 [14,19] (N = 12); NCT01548404 [14] (N = 51); NCT01639040 [14] (N = 17); NCT02260986 [10] (N = 581); NCT01979016 [18] (N = 44); NCT02210780 [15] (N = 168); NCT02277743 [12] (N = 353); NCT02407756 [16] (N = 5); NCT02395133 [22] (N = 415); NCT02277769 [12] (N = 402); NCT02755649 [11] (N = 313); NCT02647086 [17] (N = 13) b These patients completed the treatment and end-of-study periods c Includes reasons of relocation, desire for pregnancy, did not want to discontinue treatment for 12 weeks, work/school conflict, and personal reasons not specified d Includes patients withdrawn from the study, both those receiving treatment at the time of withdrawal and those not receiving treatment during the safety follow-up period e Includes the following dupilumab doses in the parent study: 75 mg qw, 100 mg q4w, 150 mg qw, 200 mg q2w, 200 mg qw, 300 mg q8w, 300 mg q4w, 2 mg/kg, 4 mg/kg f These patients had screen failed in the parent study because the enrollment target was met, but they were permitted to enter the OLE Dupilumab showed substantial and sustained improvement in AD signs and symptoms from the baseline of the parent study, with continued incremental improvement beyond 52 weeks of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The most common serious TEAEs included squamous cell carcinoma of the skin. Of note, an increased incidence of non-melanoma skin cancers in patients with AD has been reported in the literature [24][25][26]. [14,19] (N = 7); NCT01859988 [20] (N = 296); NCT01385657 [14,19] (N = 12); NCT01548404 [14] (N = 51); NCT01639040 [14] (N = 17); NCT02260986 [10] (N = 581); NCT01979016 [18] (N = 44); NCT02210780 [15] (N = 168); NCT02277743 [12] (N = 353); NCT02407756 [16] (N = 5); NCT02395133 [22] (N = 415); NCT02277769 [12] (N = 402); NCT02755649 [11] (N = 313); NCT02647086 [17] (N = 13) b These patients completed the treatment and end-of-study periods c Includes reasons of relocation, desire for pregnancy, did not want to discontinue treatment for 12 weeks, work/school conflict, and personal reasons not specified d Includes patients withdrawn from the study, both those receiving treatment at the time of withdrawal and those not receiving treatment during the safety follow-up period e Includes the following dupilumab doses in the parent study: 75 mg qw, 100 mg q4w, 150 mg qw, 200 mg q2w, 200 mg qw, 300 mg q8w, 300 mg q4w, 2 mg/kg, 4 mg/kg f These patients had screen failed in the parent study because the enrollment target was met, but they were permitted to enter the OLE Dupilumab showed substantial and sustained improvement in AD signs and symptoms from the baseline of the parent study, with continued incremental improvement beyond 52 weeks of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Many known inflammatory and pre-neoplastic disorders are associated with impaired barrier function. [1118] These include psoriasis, atopic dermatitis and actinic keratosis, the most common precursor to cutaneous squamous cell carcinoma [19,20]. Emollients are employed in the treatment of inflammatory disorders, and application of sunscreen has been shown to cause regression of actinic keratosis [21].…”
Section: Introductionmentioning
confidence: 99%
“…These results might be because these patients had many symptoms present on the skin surface, which lead them to be more concerned about their risk of skin cancer. A previous study on atopic eczema confirmed the increased risk of squamous cell carcinoma but not malignant melanoma among atopic dermatitis patients [10,11].…”
Section: Discussionmentioning
confidence: 73%